The Controversy of Using Non-Halal Ingredients in Vaccine Production: Between Emergency Needs and Sharia Principles - Renhaddwi Mahadana Satya; Najwa Rahman (Siyasah Dusturiyah: State Law Review, 2025)
The controversy surrounding the use of non-halal ingredients in vaccine production presents a complex dilemma between public health needs and adherence to Islamic principles, particularly in Muslim-majority countries such as Indonesia. This study examines how the concepts of halal compliance and the doctrine of necessity in Islamic law serve as the basis for legitimizing vaccines containing non-halal elements, especially during pandemic conditions. It also explores how halal and non-halal fatwas issued by religious authorities, particularly the Indonesian Ulema Council (MUI), shape public responses, influence vaccine acceptance, and generate economic implications for both the government and the pharmaceutical industry. Employing a normative juridical method through statutory and conceptual approaches, this research analyzes legal principles, Islamic doctrines, and positive regulations governing halal product assurance. The findings indicate that although the principle of necessity offers legal flexibility for the use of non-halal vaccines, its effectiveness heavily depends on clear public communication and the legitimacy of religious fatwas. Furthermore, the study evaluates the halal vaccine issue from a constitutional law perspective, specifically through the symbiotic paradigm of religion–state relations. It concludes that strengthening interinstitutional coordination, improving public literacy, and providing halal vaccine alternatives constitute strategic measures to ensure an inclusive and effective vaccination policy aligned with both Islamic principles and Indonesia’s constitutional framework.